Efficacy of Low Dose Topiramate and Propranolol in Migraine Prophylaxis - Khan, Muhammad Abdul Momen; Ferdous, Jannatul; Kabir, AKM Golam; Rashid, Md Mamnur; Islam, Md Enayet Ul; Khan, SM Dastegir (Journal of Shaheed Suhrawardy Medical College, 2018)
Background: Migraine, the second most common cause of headache that can significantly impair the lives of people. Various drugs are available for migraine prophylaxis but all of which have varying degrees of adverse effects that may significantly limit their use. Objectives: To observe whether low dose topiramate is more effective compared to propranolol in migraine prophylaxis. Methods: Total 120 patients the age range of 18 to 50 years were recruited as study population of migraine in the Out Patient Department (OPD) & Headache Clinic,BSMMU.60 patients were administered by Tab.Topiramate 50 mg/ day named as group-I and rest of 60 patients were administered by Tab. Propranolol 80 mg /day named as group-II. Out of them in total 96 patients had completed the study. 47 patients had completed study in group-I and 49 patients in group-II. During trial, three follow up visits were taken for both groups, 1st follow up after 4 weeks of baseline information, 2nd follow up after 4 weeks of treatment, 3rd follow up after 8 weeks of treatment. Efficacy of treatment was measured by frequency, duration and severity of headache as measured by the visual analogue scale (VAS). Results: The mean (SD) age of group-I (topiramate) and group-II (propranolol) group were found 29.72±9.58 years and 30.96±10.11 years respectively. Female sex was found predominant in both groups. At final follow up, there was statistically significant difference in mean (SD) value of frequency of migraine between topiramate and propranolol group (4.72±2.80 vs. 3.48±2.20; p=0.024]. Propranolol appeared statistically significant than topiramate [TPM 5.53±2.98 vs. PRO 4.36±1.55; p=0.047].Regarding severity of headache, better results also were observed in the propranolol group than topiramate (p< 0.05). Both drugs appeared significant in efficacy measurement (p<0.001). Patient drop out was more in the topiramate group than the propranolol group (21.68 % vs. 18.34%). Furthermore, in the topiramate group, patients complained of more adverse effects than propranolol group (23.4% vs. 14.3%), which was statistically significant. Conclusion: The present study suggests that low dose topiramate and propranolol are effective for migraine prophylaxis in reduction of frequency, severity and duration of migraine individually and propranolol appears more effective compared to that of topiramate. J Shaheed Suhrawardy Med Coll, December 2017, Vol.9(2); 49-54